Commitment to organizational career, career growth, and intention to quit: Evidence from IT professionals - Kulkarni, Sudhakar R; Nagesh, P; Bharath, Sindu; Swamy, T S Nanjundeswara (International Journal of Management and Sustainability, 2025)
The research proposes to explore the nexus between Commitment to Organizational Career (COC) and Career Growth (CG). It also examines the role of Intention to Quit (IQ) amid COC and CG among IT professionals. The antecedents of the study variables (COC, CG, and IQ) were validated using Exploratory Data Analysis. The relationships among the study variables were identified using SEM. Multiple regression analysis was adopted to examine the mediating role of IQ. COC is a single-factor construct; career growth comprises dual factors (professional development, compensation, and career goals), while IQ is a single-factor variable. The results confirm that COC influences CG; the impact of COC on CG is significant and inverse. Notably, the role of IQ is non-significant in the relationship between COC and CG. The study provides practical insights by examining the proposed mediation model and could make at least three contributions. Firstly, it explored and validated the antecedents of variables (COC, CG, and IQ). Secondly, it expanded the understanding and influence of COC on CG. Thirdly, it suggests mechanisms to drive COC to mitigate impediments to CG and reduce IQ, which can help HR professionals design effective career advancement policies. Thus, leveraging insights from this study, organizations fostering career growth and minimizing turnover risks can create a sustainable and committed workforce.